Effect of Temperature and Time to the Antioxidant Activity in Plecranthus Amboinicus Lour - M. M., Yusoff; Mohd S. Azman, Abdul Rahim; Jailani, Salihon; Ibrahim, Abu Bakar; Mohd Rizal, Martua Damanik (Asian Network for Scientific Information, 2010)
Problem statement: Processing of food involving heat will contribute to loss of nutritional content, thus it is important to measure and control temperature and time to reduce the loss.Approach: Examine the effects of variations in boiling temperature and boiling time on the antioxidant activity of the boiling extract of Plecranthus amboinicus Lour. Fresh plants were boiled at 45, 60, 100 and 120°C for 1, 2 and 3 h respectively. The decoction was then filtered and the antioxidant activities of the extracted samples were measured on the basis of the scavenging activity of the stable 1,1-Diphenyl-2-Picrylhydrazyl (DPPH) free radical scavenging assay. Results: The antioxidant activity increased with the rise of temperature from 45-100°C but dropped when the extraction temperature was raised to 120°C. Two hours boiling time gave the highest antioxidant activities, but with no significant difference compared to 1 h boiling time (p>0.05). However, 3 h of boiling gave significantly (p<0.05) less antioxidant activity in the extract. Conclusion: Knowing the best boiling temperature and time will guide the future research in preserving antioxidant content of the plant when processing by boiling.